Implementation of BUMDA (Baga Utsaha Manunggal Desa Adat) Management in Marketing and Empowering The Development of Gunung Payung Cultural Park as a Potential Tourist Attraction in Kutuh Village, Kuta South, Badung, Bali - I Made Suidarma; Komang Sri Widiantari; I Dewa Ketut Gede Prabawa; Ni Ketut Arniti (Universitas Warmadewa, 2023)
Kutuh Village currently has an integrated business entity named BUMDA (Bhaga Utsaha Manunggal Desa Adat) Management. One of the potentials possessed by the Kutuh traditional village is the Gunung Payung Cultural Park as a Tourist Attraction. Kutuh Traditional Village is now managed directly by the BUMDA management of Kutuh Village. The purpose of this research is to find out about the potentials that can be developed in Gunung Payung Tourist Attraction and how BUMDA management strategies in marketing and development are carried out at Gunung Payung Tourist Attraction. This research is a qualitative descriptive study. The data collection method used in this research is the method of observation, interviews, and documentation. The results show that there are several potentials that can be developed such as the Dhang Khayangan Temple, Gunung Tedung (Gunung Payung), white sand beach with be beautiful cliffs, monkey forests, alang alang gardens that adorn the cliffs, sports arenas such as soccer fields, jogging tracks with beautiful views as they are on a cliff, as well as a stage for cultural arts performances for the Kecak fire dance and barong dance as well as cultural attractions owned by Kutuh Village.